Credit Risk, Deposit Mobilization and Profitability of Ghanaian Banks - Akuma, John; Doku, Isaac; Awer, Nathaniel (International Journal of Economics and Financial Issues, 2017)
This paper seeks to investigate the relationship between deposit mobilization, credit risk and profitability of Ghanaian banks from 2002 to 2011. Secondary data were obtained from financial statements of 17 Ghanaian banks who have operated consistently within the study period. Panel regression analysis is used in the estimation of a function relating to the return on assets (ROA) to measures of credit risk and deposit mobilization as well a few control variables. The results reveal a significantly positive relationship between credit risk, deposit mobilization, growth in interest income, capital adequacy ratio and profitability of Ghanaian banks. However, a significantly negative relationship between year-on-year inflation and ROA was found. With regard to the relationship between bank size and profitability, the results found no significant association between the two. The research suggests that profitable banks in Ghana depend more on bank deposits as one of their main financing options. In the Ghanaian case, a high proportion (64.33%) of total liabilities is represented by bank deposits; attesting to the fact that Ghanaian banks largely depend on deposits for financing their operations. The study recommends that banks should implement effective strategies to mobilize more deposits from both the formal an informal sectors of the economy. They should also invest heavily in credit risk management. Both strategies will enhance their profitability. Keywords: Profitability, deposit mobilization and credit risk. JEL Classifications: E51, G21